Highly Sensitive Direct Detection and Quantification of Burkholderia pseudomallei Bacteria in Environmental Soil Samples by Using Real-Time PCR - Trung, T; Hetzer, A; Goehler, A; Topfstedt, E; Wuthiekanun, V; Limmathurotsakul, D; Peacock, S; Steinmetz, I (2011)
The soil bacterium and potential biothreat agent Burkholderia pseudomallei causes the infectious disease melioidosis, which is naturally acquired through environmental contact with the bacterium. Environmental detection of B. pseudomallei represents the basis for the development of a geographical risk map for humans and livestock. The aim of the present study was to develop a highly sensitive, culture-independent, DNA-based method that allows direct quantification of B. pseudomallei from soil. We established a protocol for B. pseudomallei soil DNA isolation, purification, and quantification by quantitative PCR (qPCR) targeting a type three secretion system 1 single-copy gene. This assay was validated using 40 soil samples from Northeast Thailand that underwent parallel bacteriological culture. All 26 samples that were B. pseudomallei positive by direct culture were B. pseudomallei qPCR positive, with a median of 1.84 × 10 4 genome equivalents (range, 3.65 × 10 2 to 7.85 × 10 5) per gram of soil, assuming complete recovery of DNA. This was 10.6-fold (geometric mean; range, 1.1- to 151.3-fold) higher than the bacterial count defined by direct culture. Moreover, the qPCR detected B. pseudomallei in seven samples (median, 36.9 genome equivalents per g of soil; range, 9.4 to 47.3) which were negative by direct culture. These seven positive results were reproduced using a nested PCR targeting a second, independent B. pseudomallei-specific sequence. Two samples were direct culture and qPCR negative but nested PCR positive. Five samples were negative by both PCR methods and culture. In conclusion, our PCR-based system provides a highly specific and sensitive tool for the quantitative environmental surveillance of B. pseudomallei. © 2011, American Society for Microbiology.